2021
DOI: 10.1111/jar.12962
|View full text |Cite
|
Sign up to set email alerts
|

Social educator students' readiness to address sexual health in their future profession

Abstract: Background: Norwegian social educator students' attitudes towards addressing sexual health are unknown, even if their future clients often have needs related to sexual issues. Purpose: To investigate social educator students' readiness to address sexual health in their future profession. Methods: In 2019, 213 social educator students (response rate 34%) responded to the Students' Attitudes towards addressing Sexual Health Extended online questionnaire. Results: Most of the social educator students felt comfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…PA-SH-D can probably be used by other health professionals outside rehabilitation as the PA-SH-D broadly address sexual health and not only sexual health in rehabilitation. Furthermore, the SA-SH has been translated to Norwegian and extended for Social Educator Students working with people with intellectual disabilities (27 items), 46 , 47 implying that PA-SH-D potentially can be expanded to other professionals in social care as well.…”
Section: Discussionmentioning
confidence: 99%
“…PA-SH-D can probably be used by other health professionals outside rehabilitation as the PA-SH-D broadly address sexual health and not only sexual health in rehabilitation. Furthermore, the SA-SH has been translated to Norwegian and extended for Social Educator Students working with people with intellectual disabilities (27 items), 46 , 47 implying that PA-SH-D potentially can be expanded to other professionals in social care as well.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, staff in intellectual disability services have reported that harmful sexual behaviour was challenging for them to handle (Oloidi et al, 2022 ; Ward et al, 2001 ). Further, a lack of knowledge among professional caregivers about the sexuality of people with intellectual disabilities has been documented in several studies (Esmail et al, 2010 ; Lunde, 2014 ; Lunde et al, 2022 ; Saxe & Flanagan, 2016 ; Young et al, 2012 ). Fyson and Patterson ( 2020 ), interviewing staff from residential settings, found variations in staff's understanding of abuse and poor practice.…”
Section: Introductionmentioning
confidence: 99%